ลักษณะการทำงานและบทบาทของล่ามในกระบวนการช่วยเหลือและคุ้มครองสวัสดิภาพผู้เสียหายจากการค้ามนุษย์ในประเทศไทย - ศิริพร ศิริธนชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research aims to study the working environment and role of the interpreters for protection of and assistance to victims of human trafficking. It also covers the need for interpreters, related problems and proposed solutions. The data collected mainly from the interviews. Two groups of people involved in helping and protecting victims of human trafficking were interviewed: 1) eleven interpreter users and 2) five interpreters. The research found that Thai – Burmese is the most wanted language combination, followed by Thai – Khmer. The number of quality and trusted interpreters available is inadequate, when quality interpreters would influence co-operation of victims in providing information about the trafficker as well as other information necessary for protection of and assistance to the victims themselves. The study also shows that being a professional interpreter in this field is less attractive due to the uncertain working environment, and various roles and responsibilities. In addition, there are three major issues related to interpreting services in the field: 1) interpreter’s job and income security, 2) quality of interpreters, and 3) lack of recognition. Therefore, the government and related agencies should promote and create awareness and understanding of roles of interpreters for protection of and assistance to victims of human trafficking. There should be a welfare and fringe benefit scheme as well as training programs to enhance quality of interpreters. Better quality of interpreters will enhance efficiency and effectiveness of the protection of and assistance provided for the victims of human trafficking.